Deficiency of HMGN2 enhances antibacterial activity of macrophages by promoting H3 histone modification-mediated CD14/iNOS expression - Yang, Zhen; Zhang, Xiao; Liu, Chaoqun; Huang, Ning; Teng, Yan; Miao, Junming (Frontiers in Immunology, 2025)
High-mobility group nucleosomal-binding domain 2 (HMGN2) is a widely recognized chromatin-structural protein within the nucleus of eukaryotes. It has been demonstrated to be implicated in immune responses during bacterial infection. Nevertheless, the regulatory mechanism of HMGN2 in the antibacterial process of macrophages remains unclear. In this research, distinct alterations in HMGN2 expression in macrophages were observed subsequent to microbial stimulation. To investigate the role of HMGN2 in macrophages during infection, the CRISPR-Cas9 technology was employed to construct an HMGN2-knockout RAW264.7 cell line. It was verified that HMGN2 knockout could significantly enhance the bactericidal and phagocytic capabilities of macrophages. The mechanistic investigation revealed that cluster of differentiation 14 (CD14) was transcriptionally promoted in HMGN2-knockout macrophages. HMGN2 knockout regulates CD14 expression by augmenting histone epigenetic modification levels on the CD14 gene promoter, including H3K4me3, H3K9ac, and H3K27ac. Moreover, HMGN2 knockout can activate the CD14-mediated mitogen-activated protein kinase (MAPK) signaling pathways to facilitate nitric oxide (NO) production. This study uncovers a crucial role of HMGN2 in the macrophage-mediated host immune response. HMGN2 is anticipated to serve as a therapeutic target for the treatment of infectious diseases.